Effects of the Stanford Chronic Conditions Model on Behavioral and Clinical Indicators in Saudi Arabia: A Prospective Quasi-Experimental Study - Bahari G; Kerari A; Alsadoun A; Alnassar M (Journal of Multidisciplinary Healthcare)
Ghareeb Bahari,1 Ali Kerari,1 Ahmed Alsadoun,2 Muhanna Alnassar2 1Nursing Administration and Education Department, College of Nursing, King Saud University, Riyadh, Saudi Arabia; 2Medical Surgical Department, College of Nursing, King Saud University, Riyadh, Saudi ArabiaCorrespondence: Ghareeb Bahari, Nursing Administration and Education Department, College of Nursing, King Saud University, P.O. Box 642, Riyadh, 11421, Saudi Arabia, Tel +966118054381, Email gbahari@ksu.edu.saPurpose: This study aimed to evaluate the 6-month impact of the Chronic Disease Self-Management Program based on the Stanford chronic condition model on behavioral and clinical indicators in individuals with chronic illnesses.Patients and Methods: This prospective, quasi-experimental study was conducted in primary healthcare centers located in Riyadh, Saudi Arabia. A total of 110 adults aged 18 years or older, living with at least one chronic disease, and receiving treatment at a primary healthcare center were included. We compared patients who received the Chronic Disease Self-Management Program with those who received the usual care from primary healthcare centers. Data analysis included analysis of descriptive and covariance statistics.Results: The analysis of covariance indicated that individuals who received the Chronic Disease Self-Management Program had significantly lower systolic (F=5.60, p< 0.05) and diastolic blood pressure (F=7.60, p< 0.01). These patients were more likely to adopt healthy behaviors to manage their chronic illnesses (F=11.17, p< 0.01). However, no significant differences were observed in the HbA1c values of the patients.Conclusion: We recommend incorporating the Stanford Chronic Disease Self-Management Program into patient education to foster peer support for effective chronic disease management.Keywords: blood glucose, blood pressure, chronic disease, health personnel, health status indicators